Real Perspective of Fourier Transforms and Current Developments in Superconductivity - Manuel Velazquez Arcos, Juan (IntechOpen, 2021)
This book presents a comprehensive overview of Fourier transforms and the treatment of superconductivity under the vision of the electromagnetic properties of superconductors. It begins with the latest applications and mathematical properties of Fourier transforms and the structure of quantum Fourier operators and fast summations of truncated Fourier series. Then, the book covers topics like tissue engineering, regenerative therapies, and medical imaging systems in medicine. In addition, the book addresses superconductivity subjects, the Lomb-Scargle periodogram on time series, biomedical signals, and two-dimensional Fourier series.